2016
DOI: 10.18632/oncotarget.12072
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small molecule inhibitors of ERCC1-XPF that inhibit DNA repair and potentiate cisplatin efficacy in cancer cells

Abstract: ERCC1-XPF heterodimer is a 5′-3′ structure-specific endonuclease which is essential in multiple DNA repair pathways in mammalian cells. ERCC1-XPF (ERCC1-ERCC4) repairs cisplatin-DNA intrastrand adducts and interstrand crosslinks and its specific inhibition has been shown to enhance cisplatin cytotoxicity in cancer cells. In this study, we describe a high throughput screen (HTS) used to identify small molecules that inhibit the endonuclease activity of ERCC1-XPF. Primary screens identified two compounds that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…4d ). ERCC1 is an important gene regulating DNA repair 20 , which is a downstream gene of the AKT pathway 18 . Then, we found that PFKFB3 silencing reduced expression of AKT, pAKT, and ERCC1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4d ). ERCC1 is an important gene regulating DNA repair 20 , which is a downstream gene of the AKT pathway 18 . Then, we found that PFKFB3 silencing reduced expression of AKT, pAKT, and ERCC1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation of post-translational modification and stability reported here led us to an alternative approach to target ERCC1-XPF. However, while this work was in progress, more encouraging results for conventional ERCC1-XPF inhibitors have been reported [ 43 , 44 ]. In particular, an ERCC1-XPF endonuclease inhibitor (IC50 < 1 μM), with specificity against another endonuclease and, despite only showing ˜2-fold enhanced sensitivity to cisplatin, potentiated cisplatin activity in a lung cancer xenograft model [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The site is on the XPF nuclease domain and contains a number of charged residues and metal ions, which make it an attractive target for small molecule binding. Recently, several inhibitors have been reported, some of which have been shown to enhance chemotherapy in cell and xenograft tumor models (Arora et al, ; Chapman, Gillen, et al, ; Chapman, Wallace, et al, ; Gentile, Barakat, & Tuszynski, ; McNeil et al, ). However, the similarity between catalytic sites of several human divalent cation‐based DNA‐cleaving enzymes constitutes an obstacle to designing XPF‐specific inhibitors, and an experimental structure of the human XPF nuclease domain has not been solved yet (McNeil & Melton, ).…”
Section: Introductionmentioning
confidence: 99%